REMOTE, HYBRID AND ON-SITE WORK IN ORGANIZATIONS IN BULGARIA: INTERACTIONS AND INFLUENCE ON WELL-BEING, WORK ENGAGEMENT AND WORK-LIFE BALANCE - Vihra Naydenova; Viktoriya Nedeva-Atanasova (Anthropological Researches and Studies)
Objectives. This article focuses on a relatively under-researched topic – different forms of work (on-site, hybrid and remote) in Bulgarian organizations. The aim of present study is to explore the influence of form of work on well-being, work engagement and work-life balance as well as the interactions between these phenomena. Material and methods. An online survey was conducted with 432 managers and employees from private and public organizations in Bulgaria, using three scales (UWES-9, WHO-5, WLBS) for measuring the main constructs and a questionnaire on the individual-demographic data. The Work-life Balance Scale is applied for the first time among Bulgarian sample. One-Way ANOVA, correlation and regression analyses were performed. Results. The results indicate that respondents who use hybrid and on-site form of work are more engaged (three elements Vigor, Dedication and Absorption) (p<.001), but the participants who work in a hybrid form and remotely have significantly better work-life balance (p<.001). The Bulgarian sample showed good levels of engagement compared to other cultures. No statistically significant differences were found in the well-being scores based on respondents’ form of work (p>.05). A strong positive correlation was found between the work engagement and the well-being, and a weak one was noticed between the work engagement and the work-life’s balance. The work-life’s balance positively influences the well-being (R=.465). Conclusions. The present study confirms that the hybrid work combines many beneficial elements for Bulgarian managers and employees, such as good levels of work engagement and work-life balance, opportunities for social interactions with colleagues at the office but also a flexibility to work from home a part of the week.